2021
DOI: 10.1108/bij-03-2021-0173
|View full text |Cite
|
Sign up to set email alerts
|

Destination brand equity and tourist's revisit intention towards health tourism: an empirical study

Abstract: PurposeThis paper aims to investigate the relationship between destination brand equity and tourist's revisit intention towards health tourism destinations. The study also examines the mediating effect of destination brand association between destination-based brand equity and travellers' revisit intention for health tourism destinations.Design/methodology/approachA survey instrument is used to examine the relationships in the proposed model using the co-variance-based structural equation modelling (SEM) techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 140 publications
3
10
0
Order By: Relevance
“…Depending on the research findings, it has been determined that destination awareness and destination loyalty dimensions have a strong effect on travel intention. This finding is in parallel with the results of other studies present in the literature (Rahman et al, 2021;Kumail et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Depending on the research findings, it has been determined that destination awareness and destination loyalty dimensions have a strong effect on travel intention. This finding is in parallel with the results of other studies present in the literature (Rahman et al, 2021;Kumail et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…Destination brand equity has a critical role for the destination selection process and learning how to encourage the tourists to visit specific areas is highly essential for the tourism industry. Within this context, in recent years, tourism scientists have become more aware of the importance of destination branding and an increasing number of tourism researchers have adopted the brand equity theory in their studies (Dedeoğlu, Niekerk, Weinland & Celuch 2019; Zhang et al, 2020;Rahman et al, 2021;Uslu & Ergün, 2021). This study investigates the relational link between the effect of destination brand equity dimensions on travel intention and the moderator role of nationality by means of the application of structural equation model.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Mostafa, Siamak, Ahmad and et al (2021) investigated the mediating role of tourist satisfaction in the relationship between memorable tourism experiences and behavioral intentions in heritage tourism [39]. Rahman, Sabbir, Surajit and et al (2021) aimed to investigate tourist willingness to conduct a medical tourism revisiting and suggested that stakeholders should focus on the hedonic/emotional and utilitarian/functional, and economic factors of the destination [40]. Some researchers, such as Seokho, Yoon, Ji-Hwan, and Jookyung (2021), investigated how the multidimensional components of AR experiential value (i.e., visual appeal, entertainment, enjoyment, and escapism) affect supportive behavior through AR satisfaction [41].…”
Section: Experience Value Satisfaction and Revisit Intentionsmentioning
confidence: 99%
“…In terms of medical tourism, rural tourism, adventure tourism, and sports tourism, functional value and/or contextual value positively impact emotional, economic, and cognitive value [34,35,40,42]. The correlation among the above keywords was usually found in the product market [46].…”
Section: (6) Interrelationship Of Experiential Valuementioning
confidence: 99%
“…Their results revealed that these place make a consumer surplus worth 1.24-3.64 USD per tourist in a year and, thus yield a gross recreational value 0.06-0.84 million USD per year in this region. The scholars, Rahman et al (2021), examined the destination's brand equity and tourists' revisit intention toward health tourism. Their analysis indicated that destination brand equity affects a traveler's revisit intention for medical tourists through destination brand association, and that a traveler's perceived trust, reliability, and soft concerns moderate the link between destination brand equity and destination brand association, as well as a significant moderation impact on the link between destination brand association and intention to revisitof a traveler to a health tourism destination.…”
Section: Introductionmentioning
confidence: 99%